Advantages and disadvantages of wind power plants - Roshchina, A. A. (ТДАТУ, 2021)
Many of the described problems can be solved in the process of technology development. According to the International Renewable Energy Agency, despite all the cons, at the end of 2017 the capacity of wind farms was over 18.7 GW. This is almost half of the total capacity of Ukraine’s energy facilities. So, the advantages of WPP definitely outweigh the disadvantages.
Keywords: Environmental preservation; Wind power plants